2012
DOI: 10.1590/s0100-879x2012007500134
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of SNPs in the FTO gene and predisposition to obesity in Malaysian Malays

Abstract: The common variants in the fat mass- and obesity-associated (FTO) gene have been previously found to be associated with obesity in various adult populations. The objective of the present study was to investigate whether the single nucleotide polymorphisms (SNPs) and linkage disequilibrium (LD) blocks in various regions of the FTO gene are associated with predisposition to obesity in Malaysian Malays. Thirty-one FTO SNPs were genotyped in 587 (158 obese and 429 non-obese) Malaysian Malay subjects. Obesity trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
(44 reference statements)
1
10
0
5
Order By: Relevance
“…The FTO gene is located on chromosome 16, position 16q12.2, and comprises 9 exons. This gene is expressed in the hypothalamus, at the level of the arcuate nucleus, which is responsible for appetite behavior and fatty acid metabolism, among others ( 24 , 25 ). Therefore, a recent cross-sectional study was performed on 406 Brazilian children and adolescents aged 7–17 years, among whom 34.5% were overweight or obese.…”
Section: Fat Mass and Obesity-associated (Fto) Gene And Obesitymentioning
confidence: 99%
“…The FTO gene is located on chromosome 16, position 16q12.2, and comprises 9 exons. This gene is expressed in the hypothalamus, at the level of the arcuate nucleus, which is responsible for appetite behavior and fatty acid metabolism, among others ( 24 , 25 ). Therefore, a recent cross-sectional study was performed on 406 Brazilian children and adolescents aged 7–17 years, among whom 34.5% were overweight or obese.…”
Section: Fat Mass and Obesity-associated (Fto) Gene And Obesitymentioning
confidence: 99%
“…In the Malaysian population, two studies reported associations between candidate gene polymorphisms and blood lipids in adults [15,16], while only one study on dietary patterns [17]. Hence, gene-diet interaction studies involving candidate genes and dietary patterns on risk factors of CVD such as hyperlipidemia and hypercholesterolemia are scarce in the Malaysian population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to body fat distribution traits, rs17817288 was also reported to be associated with predisposition to obesity in multiple populations 13 15 . And the associations with the combined samples were mostly contributed by the Caucasian group due to great genetic differentiation 16 .…”
Section: Discussionmentioning
confidence: 99%